Intrinsic coagulation pathway-mediated thrombin generation in mouse whole blood - Konrath, Sandra; Mailer, Reiner K.; Beerens, Manu; Englert, Hanna; Frye, Maike; Kuta, Piotr; Preston, Roger J. S.; Maas, Coen; Butler, Lynn M.; Roest, Mark; de Laat, Bas; Renné, Thomas (Frontiers in Cardiovascular Medicine, 2022)
Calibrated Automated Thrombography (CAT) is a versatile and sensitive method for analyzing coagulation reactions culminating in thrombin generation (TG). Here, we present a CAT method for analyzing TG in murine whole blood by adapting the CAT assay used for measuring TG in human plasma. The diagnostically used artificial and physiologic factor XII (FXII) contact activators kaolin, ellagic acid and polyphosphate (polyP) stimulated TG in murine blood in a dose-dependent manner resulting in a gradual increase in endogenous thrombin potential and peak thrombin, with shortened lag times and times to peak. The activated FXII inhibitor rHA-Infestin-4 and direct oral anticoagulants (DOACs) interfered with TG triggered by kaolin, ellagic acid and polyP and TG was completely attenuated in blood of FXII- (F12−/−) and FXI-deficient (F11−/−) mice. Moreover, reconstitution of blood from F12−/− mice with human FXII restored impaired contact-stimulated TG. HEK293 cell-purified polyP also initiated FXII-driven TG in mouse whole blood and addition of the selective inhibitor PPX_Δ12 ablated natural polyP-stimulated TG. In conclusion, the data provide a method for analysis of contact activation-mediated TG in murine whole blood. As the FXII-driven intrinsic pathway of coagulation has emerged as novel target for antithrombotic agents that are validated in mouse thrombosis and bleeding models, our novel assay could expedite therapeutic drug development.